Evaluating community deliberations about health research priorities. (28th June 2019) - Goold, Susan Dorr; Danis, Marion; Abelson, Julia; Gornick, Michelle; Szymecko, Lisa; Myers, C. Daniel; Rowe, Zachary; Kim, Hyungjin Myra; Salman, Cengiz
Abstract: Context: Engaging underrepresented communities in health research priority setting could make the scientific agenda more equitable and more responsive to their needs. Objective: Evaluate democratic deliberations engaging minority and underserved communities in setting health research priorities. Methods: Participants from underrepresented communities throughout Michigan (47 groups, n = 519) engaged in structured deliberations about health research priorities in professionally facilitated groups. We evaluated some aspects of the structure, process, and outcomes of deliberations, including representation, equality of participation, participants' views of deliberations, and the impact of group deliberations on individual participants' knowledge, attitudes, and points of view. Follow‐up interviews elicited richer descriptions of these and also explored later effects on deliberators. Results: Deliberators (age 18‐88 years) overrepresented minority groups. Participation in discussions was well distributed. Deliberators improved their knowledge about disparities, but not about health research. Participants, on average, supported using their group's decision to inform decision makers and would trust a process like this to inform funding decisions. Views of deliberations were the strongest predictor of these outcomes. Follow‐up interviews revealed deliberators were particularly struck by their experience hearing and understanding other points of view, sometimes surprised at the group's ability to reach agreement, and occasionally activated to volunteer or advocate. Conclusions: Deliberations using a structured group exercise to engage minority and underserved community members in setting health research priorities met some important criteria for a fair, credible process that could inform policy. Deliberations appeared to change some opinions, improved some knowledge, and were judged by participants worth using to inform policymakers.